Insurance-markets Equilibrium with Sequential Non-convex Market-Sector and Divisible Informal-Sector Labor Supply - Vasilev, Aleksandar (Journal of Mathematical Economics and Finance, 2018)
This  paper  describes  the lottery- and insurance-market equilibrium in an economy  with non-convex  market-sector employment  and  informal  sector  work.   In contrast  to Vasilev 2016a, the discrete-continuous labor supply decision  in this paper is a sequential  one,  and instead  of  home  production,  we focus  on informal  activity. The presence of non-convexity requires that an insurance market for market-sector employment  be put in operation to achieve  market  completeness.  In addition,  given that the labor  choice  for  market  work and informal-sector hours is made  in succes- sion,  the  insurance  market  for  market  employment  needs  to  close  before  the  labor supply choice  in the grey economy  is made.  This  timing is reminiscent of the results obtained  in Vasilev  2016b) and also  a direct  consequence of the sequential  nature  of the discrete-continuous sectoral  labor supply decision.